1984
DOI: 10.1021/jo00182a002
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-bound iridium catalysis. Hydrogen transfer from formic acid to unsaturated carbon-carbon bonds

Abstract: Polystyrene-bound IrCl(CO)(PPh3)2 promotes hydrogen transfer from formic acid to a variety of olefinic substances. The activity of the catalyst increases after the first few uses during which time a substrate-iridium complex is formed. Detailed kinetic studies were carried out with benzylideneacetophenone as the hydrogen acceptor. The catalysis is assumed to proceed by the following steps: (a) cleavage (dissociation) of an Ir-P bond in the supported complex ®-(PPh2) 2IrCl(CO); (b) coordination of the acceptor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

1984
1984
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The results listed in Table 4 were plotted in Figure 6. The figure indicated a rate increase up to 0.52 M of the aldehyde concentration and a rate decrease above 0.52 M. Such rate dependence has also been reported in some other related hydrogen transfer process (Beaupere et al, 1983;Azran et al, 1984;Bar et al, 1985). It suggested a first-order dependence at lower aldehyde concentration, but a nonlinear relationship at higher aldehyde concentration.…”
Section: Effect Of Aldehyde Concentrationsupporting
confidence: 78%
“…The results listed in Table 4 were plotted in Figure 6. The figure indicated a rate increase up to 0.52 M of the aldehyde concentration and a rate decrease above 0.52 M. Such rate dependence has also been reported in some other related hydrogen transfer process (Beaupere et al, 1983;Azran et al, 1984;Bar et al, 1985). It suggested a first-order dependence at lower aldehyde concentration, but a nonlinear relationship at higher aldehyde concentration.…”
Section: Effect Of Aldehyde Concentrationsupporting
confidence: 78%
“…When Boc-D-p-CIPhe was subjected to AF-CTH in CH,OH using NH: HCOO-, the reaction rate was 2.5 times faster than when the donor was NH: DCOO-. A similar conclusion was reached by Blum et al (13) for the formic acidtransfer hydrogenation of benzylideneacetophenone using a polymer bound iridium-based homogeneous catalyst.…”
supporting
confidence: 80%
“…For example, the mechanism of hydrogen transfer from formic acid to unsaturated C-C bonds utilizing a polystyrene anchored iridium complex catalyst has been shown by Blum er al. (13) to involve hydrogen transfer from the formate to iridium accompanied by loss of COz as the .h I . rate determining step.…”
mentioning
confidence: 99%
“…Blum and co-workers also developed a polymer-bound iridium hydrogen transfer catalyst, this time based on the IrCl­(CO)­(PPh 3 ) 2 complex. These researchers found that when they tested their polymer-bound iridium catalyst, ●-[(PPh 2 ) 2 Ir­(CO)­Cl] n , with formic acid as donor, the substrate allylbenzene was not hydrogenated efficiently (only 32% propylbenzene obtained).…”
Section: Transition Metal-mediated Isomerizations Of Allylbenzenesmentioning
confidence: 99%